From Ritual to Classroom: The Transposition of Islamic and Local Culture in Early Childhood Arts Education Curriculum - Arbi, Bahtiar; Jazuli, Muhammad; Wadiyo, Wadiyo; Cahyono, Agus; Adi, Brian Trinanda Kusuma (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This study explores the integration of Islamic values and Javanese cultural rituals in early childhood arts education within the Komunitas Lima Gunung in Central Java, Indonesia. It investigates how community-based rituals—such as Merti Dusun, Sungkem Tlompak, and Jaran Papat—serve as pedagogical spaces for the development of children’s aesthetic, spiritual, and socio-cognitive capacities. Addressing a gap in formal early childhood education, which often excludes local traditions and Islamic spiritual values, this study offers an alternative model rooted in cultural continuity and lived practice.Design/methods/approach –  Employing a participatory ethnographic approach, the study involved in-depth interviews, direct observation, photo documentation, and ritual participation within seven community art centers. Data were interpreted using theoretical frameworks including Vygotsky’s Zone of Proximal Development (ZPD), Funds of Knowledge, and Pedagogical Content Knowledge (PCK), to understand how children learn through culturally meaningful interaction.Findings – The study reveals that children’s engagement in ritual performance enhances their spiritual literacy, narrative cognition, and sense of belonging. These processes occur through embodied participation, intergenerational storytelling, symbolic aesthetics, and moral learning embedded in Islamic-Javanese rituals. The study also shows how the absence of formal educators is compensated by the community’s collective pedagogical roles.Research implications/limitations – This study is context-specific and based on a single ethno-regional setting. It does not measure long-term developmental outcomes or compare with other regions. However, it provides qualitative depth and cultural insight into the ways informal, non-institutional education functions effectively within Islamic and indigenous contexts.Practical implications – The findings highlight the need for integrating local Islamic cultural practices into early childhood curricula. The model suggests a framework for community-based religious-cultural education that promotes identity, empathy, and critical thinking through art.  Originality/value – This research offers a rare ethnographic insight into how Islamic-Javanese rituals function as aesthetic and moral education for young children. It challenges dominant models of early childhood education by proposing a culturally embedded, spiritually rooted, and community-led pedagogy.Paper type Research paper